Land readjustment in Denpasar, Indonesia: Effects on land management, the spatial distribution of land prices, and the sustainable development goals - Felipe Francisco De Souza; Hideki Koizumi (Asian Development Bank Institute (ADBI), 2020)
The process to introduce the idea of land readjustment to a number of Asian developing countries-mainly sponsored by the Japanese government-has been one of the most significant international collaborations in urban planning in the twentieth century. When such processes succeed, they can replace old approaches and precede significant changes within planning cultures. By reviewing such changes, it is possible to understand how the long-term implementation of the planning instrument influenced both countries' institutions and cities' environment after many years. Considering the Sustainable Development Goals proposed by the United Nations, this work discusses an important aspect attributed to land readjustment: that is, landowners have an incentive to provide a land contribution to increase public spaces, because their net land price likely increases after the urbanization process. However, this work raises the concern that in a context of increased inflation and overlapping externalities, the increase in land prices is unknown and it provides a methodology to approach this question. The goal is to understand if land price disparities can be found by comparing land readjustment project areas with areas urbanized without land readjustment yet with similar characteristics. The present work analyzes Denpasar, Indonesia, more than 30 years after its first land readjustment pilot project was started, and evaluates changes in land prices throughout time, inside and outside some project areas. On the basis of results from the difference-in-differences estimator, some initial findings suggest evidence of the land readjustment treatment effect. Indeed, the maximum effect on the increase in land prices reaches about 33% when compared with areas urbanized without the planning instrument. In particular, the concentration of higher land prices represents a strong argument in favor of land readjustment, as the projects generated more social benefits than costs. By contrast, such concentration might be a problem if projects are fully subsidized by the Indonesian government without cost recovery land, and if the government is not properly collecting property taxes from project areas to redistribute surpluses to the society as a whole. The work concludes with a list of research limitations and with a critical view on land readjustment as implemented in Denpasar, aiming to properly achieve the Sustainable Development Goals.
Keywords: R52; R31; R15; R51; 330; urban planning instruments; land readjustment; citywide impact assessment; land markets; difference-in-differences; urban economies